New design for old buildings - Hunt, Roger (RIBA Publishing, 2017)
This book is a celebration of good new design for old buildings and the SPAB philosophy that good new architecture can sit happily alongside old and is preferable to pastiche. Endorsing the value of architects who are engaged to work in the historic environment, this book explores design, materials and technical considerations in creating the best low energy, ecological and sustainable retrofits. It has never been more important to understand how old buildings can be adapted to make them useful and sustainable in the future. Showcasing the best examples of imaginative design and best practice, this book illustrates how old buildings can be made sustainable through the best new design and puts these design exemplars into a historical and philosophical context. With illustrative case studies and interviews throughout, including formal buildings, churches, domestic buildings, commercial, industrial and agricultural from all periods in the UK, 'New Design for Old Buildings' provides essential guidance on good, imaginative new design for old buildings.